Causes of Early Marriage in Banjar Regency, Martapura District, City - Astuti, Endang; Abbas, Ersis Warmansyah; Rusmaniah, Rusmaniah; Rahmia, Sovia Husni; Syarifuddin, Syarifuddin (Universitas Lambung Mangkurat, 2024)
The Early marriage is a marriage that occurs at a very young age, based on law 16 of 2019 where early marriage occurs at the age of 19 for men and women. Where children who marry young are often not physically mentally or emotionally mature. However, the facts researched at the Religious Affairs Office (KUA) of Martapura District, a city in Banjar Regency, where there are still many rates of early marriage, in the last 2 years from 2022-2023, even though it has been prohibited in Law 16 of 2019. Early marriage will still be allowed if there is a dispensation letter by the religious court. The purpose of this study is to be able to know. The impact of early marriage at the Religious Affairs Office in Banjar Regency, Martapura Kota District. And the researcher uses a qualitative research approach where the researcher tries to gain an understanding of the phenomenon in the problem being studied and in clarity of the statementor reality about the impact found, namely positive impact and negative impact.